Pengembangan Sistem Informasi Kerja Sama Limjamsos Berbasis Web di Dinas Sosial Aceh - Maudiva, Nabila; Ismail; Sofyan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This research develops a web-based information system for managing partnership data in Linjamsos at the Social Service Office of Aceh. The manual process, which relies on spreadsheets, has been found inefficient, prone to errors, and difficult to monitor in real-time. The web-based system is designed to enhance efficiency, accuracy, and ease of access for both the Social Service staff and partner organizations. The development process follows the Waterfall model, including stages of requirement analysis, design, implementation, and testing. Test results show that the system meets functional, performance, security, and usability criteria. Additionally, the system accelerates data management, provides transparency, and simplifies access for all stakeholders involved in Linjamsos partnerships. With the implementation of this new system, the management of social assistance and inter-agency collaboration in Aceh can be more structured and effective.